2002
DOI: 10.1111/j.1574-695x.2002.tb00565.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenic protein variations ofClostridium chauvoeicellular antigens associated with the culture growth phase

Abstract: The immunoprotective capacity of four Clostridium chauvoei strains at different growth stages is reported. In all the strains tested, the cells coming from the stationary phase were those with the highest immunoprotective capacity and, depending on the strain, this protective capacity diminished or even disappeared in other phases. Protein profiles were similar in all the strains and few proteins were differentially expressed during growth as shown by SDS-PAGE. For strain 17, a local strain, a clear relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Vaccines against blackleg consist of chemically inactivated bacteria of mostly relatively ancient strains providing outer membrane proteins and flagellar proteins that have been proposed as immunogens and bacterial culture supernatants that are expected to contain the main toxins (Mattar et al, 2002; Uzal, 2012). Recently it has been shown that the CctA toxin alone, which is conserved between C. chauvoei strains isolated worldwide, prepared by recombinant gene technology, provided full protection in a guinea pig infection model which serves as biological test for potency tests in the batch release procedure of commercial vaccines (Frey et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Vaccines against blackleg consist of chemically inactivated bacteria of mostly relatively ancient strains providing outer membrane proteins and flagellar proteins that have been proposed as immunogens and bacterial culture supernatants that are expected to contain the main toxins (Mattar et al, 2002; Uzal, 2012). Recently it has been shown that the CctA toxin alone, which is conserved between C. chauvoei strains isolated worldwide, prepared by recombinant gene technology, provided full protection in a guinea pig infection model which serves as biological test for potency tests in the batch release procedure of commercial vaccines (Frey et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Cellular antigens of C. chauvoei can be subdivided into somatic antigens and flagellar antigens. Somatic antigens are related to bacterial cells and include agglutinogenic antigens, heat-stable O antigens, non-agglutinogenic antigens, and heat-labile antigens, which do not present the O and HO antigens [17,53]. Flagellar (H) antigens are thermolabile, and two distinct ones have been identified.…”
Section: Cellular Antigensmentioning
confidence: 99%